Controle genético da resistência da lagarta-do-cartucho ao milho expressando proteínas Cry1A.105 e Cry2Ab2 - Senete, Constantino Tomás (2016)
The Spodoptera frugiperda species is considered one of the most destructive insect pests of maize crop in the Americas. Experiment with full-sib progenies and another with two populations were conducted separately in the laboratory. The experiment aims to study the predicted heritability and responses to selection realized on characters associated to resistance of this insect to the Cry1A.105 and Cry2Ab2 proteins. In both experiments larvae were fed with maize leaves expressing Cry1A.105 and Cry2Ab2 proteins until it reaches the pupal stage. When the adults emerged it was recorded percentages of survivors of each generation. In the experiment for the prediction of heritability, full-sib progenies were formed from a population collected in Sinop - MT while for the gains it was used two populations, one already mentioned and the other collected in SeteLagoas - MG. Because it is survival data (proportion of individuals surviving in function of Cry1A. 105 and Cry2Ab2 proteins) and very unbalanced data, for this character was considered the generalized linear model and a binomial distribution. For other characters the analysis considered normal distribution. The largest proportion of the variability observed in these progenies for survival in the selection pressure with the Cry1A. 105 and Cry2Ab2 proteins were expressed in maize due to genetic causes. Large magnitude of heritability was observed for all evaluated characteristics. The prediction of heritability and selection gain was observed good reliability in the evaluation and prediction of genetic parameters (high accuracy), a linear relationship between survival and other characters (larval period, lethal period and pupa biomass) and with it the response for the selection was influence for these characters, having about six days for larval period and about 10 milligrams for pupae biomass. The response to selection for survival was 3.17%. The estimate for the response to selection made in the population collected in Sinop - MT showed high potential to provide offspring adapted to Cry1A. 105 and Cry2Ab2 proteins contrary the population collected in Sete Lagoas -MG.